2022
DOI: 10.1021/acsami.2c04167
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nonlinear Behavior of Ionic Liquid-Based Reservoir Computing Devices

Abstract: Herein, a physical reservoir device that uses faradaic currents generated by redox reactions of metal ions in ionic liquids was developed. Synthetic time-series data consisting of randomly arranged binary number sequences ("1" and "0") were applied as isoscelestriangular voltage pulses with positive and negative voltage heights, respectively, and the effects of the faradaic current on short-term memory and parity-check task accuracies were verified. The current signal for the first half of the triangular volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Apart from a contribution of the fundamental knowledge, the results presented in this work may be used to better understand and further improve certain technological processes that rely on falling liquid films. Yet, the demonstrated immunity of the solitary-like waves to external vibration and their intriguing nonlinear dynamical behaviour will be of interest to researchers working on emergent technologies, where both solitary waves and fluidic systems play an important role [7,8,12,48,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a contribution of the fundamental knowledge, the results presented in this work may be used to better understand and further improve certain technological processes that rely on falling liquid films. Yet, the demonstrated immunity of the solitary-like waves to external vibration and their intriguing nonlinear dynamical behaviour will be of interest to researchers working on emergent technologies, where both solitary waves and fluidic systems play an important role [7,8,12,48,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these features, liquid-based memory devices have the potential to be emerging devices for sensing and synaptic applications. Liquid-based devices provide the advantage of emulating synaptic characteristics because synaptic functions are realized by the movement of ions and neurotransmitters between the cerebrospinal fluid and neurons in the biological synapse. ,,, For instance, the ion concentration of the liquid-based memory devices was controlled by applying electrical stimuli to emulate the synaptic functions using ion reservoirs . The conductivity of the device was controlled by varying the concentration of the ions in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3(b) shows the outcome of the parity check test that produces P C = 12.4 bits. In the literature on physical RC systems, the value of P C is usually slightly smaller than the value of M C and, typically, it reaches 2 bits [16,28,37,38]. The value of P C for algorithmic RC systems is larger than that of physical RC systems [36].…”
mentioning
confidence: 99%
“…Although in the framework of LSM the analogy between a reservoir and a liquid was made rather at an abstract level [3], follow-up research works have demonstrated that physical liquids inherently possess all characteristics required for the creation of a reservoir [10][11][12][13][14][15][16]. There have also been theoretical proposals [17][18][19][20] of RC systems based on optical solitons [21].…”
mentioning
confidence: 99%